Efficacy of fungicides against black leaf spot of ber caused by Isariopsis indica (Indian Journal of Arid Horticulture, 2013)
Ber (Zizyphus mauritiana Lamk.) occupies as an  important fruit crop of arid and semi-arid region and its  plantation is increasing gradually every year in India. Its  cultivation on marginal land with poor soil conditions can  give very good revenues with less input. However, the  major constraints in higher production are attack of  diseases and it has been observed that some of the diseases  (leaf spot and fruit rot) and post harvest diseases are  concern with productivity and economic yield in this crop.
Keywords: Mancozeb 0.2%; Difenconazole